Elaboración de una guía para el manejo en la rehabilitación de tendinopatías aquiliana en los atletas del Instituto de Deportes y Recreación de La Estrella (INDERE) durante el año 2008 (2008)
The objetive of this work is to realice for how to hangle a rehab program for injures that hapen in the tendón of Aquiles, such as bursitis,tendonitis from the Aquiles tendón that afected the sports peoples of INDERE(Institute of sports and recreación of La Estrella) country during year 2008. The injures in the tendón of Aquiles are produce for factors as bad pair of shoes, grounds or fields no desined for sports practices, a program of training or inificient work out. With respect of fisioteraphy treat ment pretend at first time lesser the pain and inflamation that produce the first fase of the injure true techniques of creotheraphy, pulse ultrasound and the tens in continue modul. The muscular recuperation and the proporcions are determinants in the recuperation of the injure and prevention of repetitives injuries and cronics Aquiles heel.